The Influence of Marketing Communications on Customer Loyalty At PT. Citra Van Titipan Kilat (TIKI) Cabang Sumedang - Sutisna, Nana; Yuniawati, Ayi Srie; Ginanjar, Yayat (Journal of Bussines Management Basic, 2025)
Marketing communication can be an effective form of communication channel to handle consumer complaints effectively and efficiently. By paying attention to the importance of marketing communication, companies can design more effective communication strategies to achieve their marketing goals, and can build strong customer loyalty. In this study, the method used is the quantitative method. According to Priyono (Sahir, 2021:13) "Quantitative research methods are scientific thinking in which there is a process of forming ideas and ideas are strictly enforced using nomometric principles and using deductive patterns". Marketing Communication (X) has a positive and significant influence on Customer Loyalty (Y) at PT. Citra Van Titipan Kilat (TIKI) Sumedang Branch with a total influence of 48.9% while is the influence of other variables that were not studied in this study. Then, based on the t-test, t is calculated as 9.679 and degrees of freedom (n-k-1) or 100-1-1= 98 is obtained from t table 1.984, so t is calculated > t table (9.679 >1.984). This means that H0 is rejected and H1 is accepted, so there is a positive and significant influence